2003
DOI: 10.1046/j.1471-4159.2003.02058.x
|View full text |Cite
|
Sign up to set email alerts
|

Polarized actin bundles formed by human fascin‐1: their sliding and disassembly on myosin II and myosin V in vitro

Abstract: Fascin-1 is a putative bundling factor of actin filaments in the filopodia of neuronal growth cones. Here, we examined the structure of the actin bundle formed by human fascin-1 (actin/ fascin bundle), and its mode of interaction with myosin in vitro. The distance between cross-linked filaments in the actin/ bundle was 8-9 nm, and the bundle showed the transverse periodicity of 36 nm perpendicular to the bundle axis, which was confirmed by electron microscopy. Decoration of the actin/fascin bundle with heavy m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
86
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(102 citation statements)
references
References 54 publications
13
86
1
Order By: Relevance
“…The bundles showed transverse periodicity of 36.9 nm, roughly corresponding to the crossover distance of the actin filament (35.7 nm) (16). Our observations are generally consistent with a previous study of wild type fascin-actin bundles (17), but contrary to these authors, we found that the transverse pattern occurred at an angle of 63.0 Ϯ 6.23° (Fig. 2B and Table 2) and not perpendicular to the bundle axis as they had reported.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The bundles showed transverse periodicity of 36.9 nm, roughly corresponding to the crossover distance of the actin filament (35.7 nm) (16). Our observations are generally consistent with a previous study of wild type fascin-actin bundles (17), but contrary to these authors, we found that the transverse pattern occurred at an angle of 63.0 Ϯ 6.23° (Fig. 2B and Table 2) and not perpendicular to the bundle axis as they had reported.…”
Section: Resultssupporting
confidence: 91%
“…Most likely, fascin binds at the interface between actin subunits in the filament, a location where most actin-binding proteins bind (25,26), bridging the narrow area of neighboring filaments. Another observation made here is that the transverse periodicity in wild type fascin-actin bundles occurs at an angle of ϳ63.0°, which is in agreement with a study of reconstituted bundles formed by mouse fascin (18) but disagrees with another study that found that the repeat is perpendicular to the bundle axis (17). Our results thus suggest that neighboring filaments in the bundle are either uniformly rotated or staggered by ϳ4.1 nm, which could help accommodate fascin molecules in the tight bundle.…”
Section: Discussionsupporting
confidence: 62%
“…It is thus reasonable to assume that no individual filament coexists with the bundles. Authors have observed that for a molar ratio [fascin]/[actin] > 0.25, which is the case here, the number of filaments in a bundle saturates to 20 (22,23). Because about 45 bundles are visible in the image of Fig.…”
Section: Significancesupporting
confidence: 63%
“…Fascin also preferentially makes parallel bundles in vitro (Fig. 1F) (35,41,43) and localizes to cellular structures composed of parallel bundles including filopodia (60,61). Fission yeast Fim1 localizes to endocytic patches composed of branched filaments with barbed ends thought to be oriented toward the membrane as well as the contractile ring composed of antiparallel bundles of filaments and likely actin cables composed of parallel filaments (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, fascin creates bundles composed exclusively of parallel filaments (Fig. 1F, supplemental Movie 6) (35,43). Because Fim1 binds to structures composed of both parallel and antiparallel filaments in vivo, this may be an essential feature of Fim1.…”
Section: -E)mentioning
confidence: 99%